Elucidation of Various PWM techniques for a Modified Multilevel Inverter - C.R. Balamurugan; S.P. Natarajan; R. Bensraj (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
This paper focuses on hybrid H-bridge cascaded MLI using two equal dc sources in order to produce a five-level output. The proposed topology reduces the number of dc sources and switching elements. This paper emphasis on various Inverted Sine Carrier PWM (ISCPWM) techniques with equal amplitude and unequal amplitude carriers. The Inverted Sine Carrier Pulse Width Modulation (ISCPWM) technique enhances the fundamental output voltage particularly at lower modulation index ranges with reduction in Total Harmonic Distortion (THD) and switching losses. Simulation is performed using MATLAB-SIMULINK. From the simulation it is observed that Variable Amplitude Inverted Sine Carrier Variable Frequency (VAISCVF) strategy provides output with relatively low distortion for all strategies. It is also seen that Variable Amplitude Inverted Sine Carrier Phase Disposition (VAISCPD) is found to perform better for all strategies since it provides relatively higher fundamental RMS output voltage.